2009
DOI: 10.1103/physrevlett.102.148102
|View full text |Cite
|
Sign up to set email alerts
|

Vesicles in Poiseuille Flow

Abstract: Blood microcirculation critically depends on the migration of red cells towards the flow centerline. We identify theoretically the ratio of the inner over the outer fluid viscosities lambda as a key parameter. At low lambda, the vesicle deforms into a tank-treading ellipsoid shape far away from the flow centerline. The migration is always towards the flow centerline, unlike drops. Above a critical lambda, the vesicle tumbles or breaths and migration is suppressed. A surprising coexistence of two types of shape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 26 publications
10
109
0
Order By: Relevance
“…The strain rate is given as _ c ¼ 2y 0 a where y 0 is the distance between the center of the polymer and the flow axis and a is a measure of the curvature of the flow profile. 22 Simple shear flow on the other hand describes fluid flow characterized by a velocity gradient perpendicular to the flow field ( Figure 1). It is modeled as a linear superposition of rotational flow with vorticity x, and elongational flow with strain rate _ c ¼ @v x @y .…”
Section: Studying the Effect Of Shear Flow On Proteinsmentioning
confidence: 99%
“…The strain rate is given as _ c ¼ 2y 0 a where y 0 is the distance between the center of the polymer and the flow axis and a is a measure of the curvature of the flow profile. 22 Simple shear flow on the other hand describes fluid flow characterized by a velocity gradient perpendicular to the flow field ( Figure 1). It is modeled as a linear superposition of rotational flow with vorticity x, and elongational flow with strain rate _ c ¼ @v x @y .…”
Section: Studying the Effect Of Shear Flow On Proteinsmentioning
confidence: 99%
“…In these models, it is presumed that the lift force always acts in the opposite direction of the wall to push the particle towards the centerline. Indeed, analytical 126 and numerical 127 studies have shown that vesicles, unlike surfactant-free drops, always migrate towards the central axis in Poiseuille flow, regardless of the value of the viscosity ratio. Exploiting deformability-induced particle migration opens new ways to focus and separate cells based on their inherent structural characteristics which results in passive, label-free cell sorting processes in microfluidics.…”
Section: Deformability-selective Cell Separationmentioning
confidence: 99%
“…We believe that when studying the motion through narrow constrictions resistance to shear should be taken into account given the large viscous shear stresses that induce large deformations. Nevertheless there is a wealth of numerical studies on the motion of vesicles in shear flows which led to the observation of discocytes and slippers shapes in a Poiseuille flow [21][22][23].…”
Section: Introductionmentioning
confidence: 99%